The biogeochemical characteristics of phosphorus in coastal sediments under high salinity and dredging conditions. (January 2019) - Zhao, Guoqiang; Sheng, Yanqing; Jiang, Ming; Zhou, Haoyuan; Zhang, Huichao
Abstract: The geochemistry of phosphorus (P) can usually be related to prevailing environmental conditions. To investigate sedimentary P cycling mechanism and biogeochemical characteristics under high salinity and dredging conditions in polluted coastal sediments, thirty-three surface sediment samples were collected from the Jiehe River (JH), Jiaolai River (JL) and their estuarine and offshore areas in the Bohai Sea. Analyses included the Standards, Measurements and Testing method (SMT), Ivanoff organic P (OP) fractionation, and nuclear magnetic resonance ( 31 P-NMR) of soluble P and indicated that HCl-P was the dominant fraction in sediments under high salinity stress. However, under dredging conditions in freshwater river sediments, NaOH-P was the dominant fraction. The potential activity of the OP fraction was reactive in freshwater river sediments, while it was unreactive under high salinity conditions. NaOH-P and HCl-P were found to be mainly derived from anthropogenic inputs, whereas both in-situ biological and anthropogenic inputs were important sources of the OP fractions. High salinity had the potential to increase NaOH-P content in acidic river sediments, resulting in the OP being relatively stable with a low risk level. Sediment dredging potentially increased the regeneration of P from HCl-P and OP and increased the potential activity of OP and IP. Seawater was found to induce removal of the NaOH-P and OP from offshore sediments, resulting in the regeneration of the remaining P at a low level. Graphical abstract: Highlights: River and coastal sediments were analyzed to characterize P pools and forms. High salinity kept the OP at a low content and promoted to increase Fe/Al-P content in acid river sediments. Sediment dredging regenerated P from Ca-P and OP, and increased the potential activity of OP and IP. Seawater could induce removal of the Fe/Al-P and OP from offshore sediment.